SCREENING OF COLLEGE STUDENTS FOR OBESITY - Memon, Sohel; Nekkanti, Vineela; Ap, Ravinandan; R, Srinivasan; Dev, Apoorva; Sharma, Sanjay (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  A prospective, cross-sectional study on the prevalence of overweight and underweight among students at an institute in Bengaluru, was conducted by estimating their body mass index. The study was carried out on 121 students in the age group of 14-28 years. Of 121 students, 35 (28.92%) were underweight, 73 (60.33%) were normal weight and 13 (10.74%) were overweight. Based on the age group, 14-20 years of age group, 28 (38.8%) were underweight, 48 (55.5%) were normal weight and 4 (5.5%) were overweight. In age group of 21-25 years, 7 (15.5%) were underweight, 32 (71.11%) were normal weight and 6 (13.33%) were overweight and in age group 25-28 years, 0 (0%) were underweight, 1 (25%) were normal weight and 3 (75%) were overweight. The study concludes that the prevalence of underweight is higher than overweight among the college students. Keywords: Prevalence, Overweight, Underweight and Body mass index.